2010
DOI: 10.1210/en.2009-1092
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Fat Determines Metabolic Profile and the Magnitude of Endocannabinoid Inhibition of the Stress Response in Neonatal Rat Offspring

Abstract: Endocannabinoids (eCBs) are products of phospholipid (PL)-derived arachidonic acid (AA) that regulate hypothalamus-pituitary-adrenal axis activity. We hypothesized that differences in the quality and quantity of maternal dietary fat would modulate the PL AA content in the neonatal brain affecting stress responsiveness via differences in eCB production and activity in stress-activated brain areas. Pregnant rats were fed a 5% [control (C)] or 30% fat [high fat (HF)] diet rich in either n-6 (HF-n-6) or n-3 (HF-n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 57 publications
4
50
1
Order By: Relevance
“…We also highlight that maternal dietary choices during pregnancy can program fetal pancreas development by altering eCB bioavailability (48,77), which prospectively determines the offspring's sensitivity to metabolic stressors. This observation has clinicopathological significance by pointing to an increased risk of diabetes in either malnourished or obese mothers and underpins the clinical potential of tissue-selective regulation of eCB levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also highlight that maternal dietary choices during pregnancy can program fetal pancreas development by altering eCB bioavailability (48,77), which prospectively determines the offspring's sensitivity to metabolic stressors. This observation has clinicopathological significance by pointing to an increased risk of diabetes in either malnourished or obese mothers and underpins the clinical potential of tissue-selective regulation of eCB levels.…”
Section: Discussionmentioning
confidence: 99%
“…eCBs are derived from arachidonic acid (20:4), an ω-6 PUFA. Correspondingly, ω-3 PUFAenriched diet during pregnancy lowers 2-AG and AEA levels in the fetus (48). ω-3 PUFA intake is also beneficial for insulin secretion and sensitivity (49)(50)(51).…”
Section: -Ag Signaling Modulates β Cell Survival In Pancreatic Pseudmentioning
confidence: 98%
“…Thus, prenatal and postnatal exposure to restricted omega-3 diet has been associated to impaired endocannabinoid-mediated neuronal functions in the adult brain, together with behavioral abnormalities [36]. Moreover, exposure to a maternal diet rich in n-3 or n-6 fatty acids modifies arachidonic acid and/or endocannabinoid levels in neonatal hypothalamus and hippocampus, resulting in alterations in the hypothalamus- pituitary-adrenal axis functions [44]. Therefore, this piece of evidence suggests that an inadequate endocannabinoid signaling resulting from exposure to an unbalanced maternal diet, might disrupt the establishment of functional circuitries involved in metabolism, learning and emotional control, leading to metabolic and neurobehavioral abnormalities later in life [27].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the effects of maternal obesity on stress reactivity, and those which have examined hypothalamic-pituitary-adrenal (HPA) axis reactivity have mainly reported short-term effects during development [8,9]. Importantly, Trottier et al [9] found that maternal hypernutrition blunts the stress response in neonatal pups while increasing stress reactivity during adolescence.…”
Section: Introductionmentioning
confidence: 99%